Peran Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Bengkel Sumber Jaya Motor : The Role of Service Quality and Price on Customer Satisfaction at the Sumber Jaya Motor Workshop - Junengsih, Junengsih; Rasyid, Aliy; Wijaya, Adrian (OGZ Research & Publishing, 2025)
Abstract:Objective: This study aims to analyze the influence of service quality and price on customer satisfaction at the Sumber Jaya Motor Workshop. The background of this study is based on the importance of improving service quality and setting appropriate prices to create customer satisfaction and loyalty.Methodology: The research method used was quantitative with a descriptive-verifiable approach. Data were collected through questionnaires distributed to customers of the Sumber Jaya Motor Workshop, then analyzed using bootstrapping techniques to determine the effect of the independent variables on the dependent variable.Research Results: The results showed that service quality (X1) had no effect on customer satisfaction, and price (X2) did. Both variables explained 69.2% of the variation in customer satisfaction, while other factors influenced the remaining 30.8%. This finding implies that although service quality and price are considered standard by consumers, both still play an important role in maintaining customer satisfaction. Therefore, improving service aspects and setting competitive prices are necessary to maintain customer loyalty.Keywords: Service quality, Price, Customer satisfaction, Workshop, Loyalty.